2014
DOI: 10.1371/journal.pone.0087017
|View full text |Cite
|
Sign up to set email alerts
|

Association between APOC1 Polymorphism and Alzheimer’s Disease: A Case-Control Study and Meta-Analysis

Abstract: BackgroundPrevious association studies examining the relationship between the APOC1 polymorphism and susceptibility to Alzheimer’s disease (AD) have shown conflicting results, and it is not clear if an APOC1 variant acts as a genetic risk factor in AD etiology across multiple populations.MethodsTo confirm the risk association between APOC1 and AD, we designed a case-control study and also performed a meta-analysis of previously published studies.ResultsSeventy-nine patients with AD and one hundred fifty-six un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 32 publications
2
47
2
Order By: Relevance
“…Little is known about the specific role of APOC1 in AD; however, as it is also a lipid carrier transport protein that, like APOE, is known to recruit the innate immune system, it may also have a role in regulation of microglial activation. More specifically, there are isolated studies which demonstrate linkage between APOC1 and declining cognition and memory in specific ethnic groups [59,60]. Consistent with the APOC1 role in lipid transport and immune activation, our expanded cell process enrichments specifically identified phagocytosis and activation of immune response (Fig.…”
Section: Apoc1 -Ceacam19 -Clptm1 Chr19supporting
confidence: 73%
See 1 more Smart Citation
“…Little is known about the specific role of APOC1 in AD; however, as it is also a lipid carrier transport protein that, like APOE, is known to recruit the innate immune system, it may also have a role in regulation of microglial activation. More specifically, there are isolated studies which demonstrate linkage between APOC1 and declining cognition and memory in specific ethnic groups [59,60]. Consistent with the APOC1 role in lipid transport and immune activation, our expanded cell process enrichments specifically identified phagocytosis and activation of immune response (Fig.…”
Section: Apoc1 -Ceacam19 -Clptm1 Chr19supporting
confidence: 73%
“…While APOC1, CEACAM19, and CLPTM1 are associated with AD, both in this study and previous studies [60][61][62], a causal association to AD remains unclear. However, there is a small literature pointing to a role for CLPTM1 in the regulation of GABA receptor trafficking from the ER to the plasma membrane, suggesting that CLPTM1 could regulate inhibitory neurotransmission [63,64].…”
Section: Apoc1 -Ceacam19 -Clptm1 Chr19contrasting
confidence: 55%
“…Our target was a 41-nt fragment of Apolipoprotein C1 (APOC1) mRNA (APOC1_41), a biomarker associated with the occurrence of Alzheimer’s disease. 4244 We designed a second nanocarrier (referred to as Carrier2) to bind a fragment of APOC1_41 with its complementary PNA fragment (Table S1) and have the same polycationic peptide tag as Carrier1. In our nanopore experiments, we found the Carrier2•APOC1_41 complex to block the ionic current much more effectively ( I / I 0 =31.3±1.5%, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The expression regulation of other genes within the 19q13.32 region in relation to human diseases also has been investigated. For example, it has been shown that cis -modulation of APOC1 expression contributes to LOAD susceptibility [30], and that TOMM40 -mRNA levels are increased in LOAD brains and regulated by an intronic poly-T variant [2527]. These findings suggest that the genetic pleiotropic effect is mediated by molecular mechanisms of gene expression regulation including, but not limited to, transcriptional regulation.…”
Section: Introductionmentioning
confidence: 99%